Integrated NV Center-Based Temperature Sensor for Internal Thermal Monitoring in Optical Waveguides - Yifan Zhao; Shihan Ding; Shuo Wang; Yiming Hu; Hongliang Liu; Zhen Shang; Yongjian Gu (Sensors)
Color centers in solids, such as nitrogen-vacancy (NV) centers in diamonds, have gained significant attention in recent years due to their exceptional properties for quantum sensing. In this work, we demonstrate an NV center-based temperature sensor integrated into an optical waveguide to enable internal temperature sensing. A surface-cladding optical waveguide was fabricated in a diamond wafer containing NV centers using femtosecond laser direct writing. By analyzing the resonant peaks of optically detected magnetic resonance (ODMR) spectra, we established a precise correlation between temperature changes induced by the pump laser and shifts in the ODMR peak positions. This approach enabled temperature monitoring with a sensitivity of 1.1 <semantics>mK/<msqrt>Hz</msqrt></semantics>. These results highlight the significant potential of color centers in solids for non-contact, micro-scale temperature monitoring.